2019
DOI: 10.5539/elt.v12n5p88
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions Towards the Benefits and Drawbacks of EMI Classes

Abstract: Globalization and internationalization have fostered the development of English as a medium of instruction (EMI). EMI is gaining its popularity all over the world. In line with this tendency, various universities in Vietnam introduce EMI to its undergraduate programs in forms of advanced or high-quality training programs. However, little research has been conducted to discover the benefits as well as drawbacks of these EMI programs, especially in context where English is not a second language nor popularly use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 20 publications
9
53
0
Order By: Relevance
“…Furthermore, too large a group of students indicated that they feel their current level of English does not allow them to benefit fully from EMI courses both in terms of content and language teaching, is an unfortunate finding, but this should not surprise us; since it confirms the earlier findings (Phuong & Nguyen, 2019).…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, too large a group of students indicated that they feel their current level of English does not allow them to benefit fully from EMI courses both in terms of content and language teaching, is an unfortunate finding, but this should not surprise us; since it confirms the earlier findings (Phuong & Nguyen, 2019).…”
Section: Discussionsupporting
confidence: 60%
“…Additionally, using English to teach non-English native speakers can impede discussion among students, putting those who struggle with the language in a disadvantageous position. As a result, EMI can lead to lower graduation rates (Byun, Chu, Kim, Park, Kim, & Jung, 2011;Airey & Linders, 2007;Collins, 2010;Al-Issa, 2017;Querol-Julián, & Camiciottoli, 2019;Phuong, & Nguyen, 2019). Two-third of the interviewees who participated in this study had positive views about EMI as they believed that it helped them to improve their English language skills and that it would help them considerably in their future employment and studies.…”
Section: Findings and Discussionmentioning
confidence: 96%
“…Purposive sampling was used as it entails studying information-rich cases and yields insight and in-depth understanding rather than empirical generalisations (Patton, 2002). Purposive sampling aims at capturing and describing the central themes across the case under study (Patton, 2002).…”
mentioning
confidence: 99%
“…Undoubtedly, the former has always drawn much of the researchers' attention. Having said that, however, numerous studies have also reported the implementation of the latter around the world so far (Chou, 2018;Malmström, Pecorari & Gustafsson, 2016;Pecorari, Shaw, Irvine & Malmström, 2011;Phuong & Nguyen, 2019;Pun & Macaro, 2019;Rose, Curle, Aizawa & Thompson;Simbolon, 2017;Wu, 2006).…”
Section: Background Of Emi In Turkeymentioning
confidence: 99%